The Empowering Disabled Communities as Creative Economy Actors Through Social Education Recreation at the Bina Siwi Orphanage: Pemberdayaan Masyarakat Disabilitas Sebagai Pelaku Ekonomi Kreatif Melalui Rekreasi Edukasi Sosial di Panti Asuhan Bina Siwi - Kenanga Kusuma Murdiyani; Yanuar Agung Fadlullah; Sahid Ramandhani; Muhammad Kholili Abdul Wahab (Universitas Veteran Bangun Nusantara, 2025)
People with disabilities have potential and skills that can be trained. One place to develop disability skills is the private foundation Bina Siwi Orphanage located in Yogyakarta. Bina Siwi Orphanage trains various disability skills such as self-help skills, arts, agriculture, animal husbandry, and making crafts. Most of the people with disabilities at Bina Siwi Orphanage have limited intellectual barriers, therefore the training provided must be accompanied by continuous skill distribution. Based on these problems, researchers conducted an experiential tourism-based educational tourism development programme. Tourism becomes an attraction because it can accommodate disability skills, has sustainable economic potential, and builds public awareness of disabilities. Tourism is developed using the Asset-Based Community Development (ABCD) approach with the stages of observation, designing educational tourism based on activities developed into tour packages, training in the management of tourism activities to the administrators of disability homes, training in marketing and promotion of tourism activities, implementation of tourism activities, and evaluation. The developed tour packages use memorable tourism experience attributes to attract tourists to visit again. The result of the programme is a package of social education recreational tourism activities. Based on the trials conducted, the most effective scheme in the implementation of the programme is the social education recreation tourism activity package. Keyword: Disabled Community, Creative Economy, Social Educational Recreatio